The Art of Successful Information Systems Outsourcing - Gefen, David (Business Expert Press, 2012)
As with other pressing issues of information systems (IS) management, managing IS outsourcing also began as a solution to industry needs, and much of this book is accordingly based on industry experience cloaked as it were in academic theory garb to add depth to these proven practices as well as allow for borrowing insight from other academic disciplines. With this approach in mind, after a quick review of what IS outsourcing is in chapter 1 and its topology in chapter 2, the book delves into this technology imperative as a core driver of IS outsourcing beyond the cost savings aspect central in other types of outsourcing, in chapter 3. The technology imperative explains why IS outsourcing is also as much about acquiring capabilities that cannot be quickly acquired or indeed planned for in advance because of the revolutionary advances in technology. This unique perspective on IS outsourcing also makes it unique from other types of outsourcing, and the remainder of the book addresses these unique issues from a head-on practitioner perspective while adding a broader theoretical perspective. It is this uniqueness of IS management that also makes the search for a boilerplate methodology that may apply across scenarios as futile as searching for a silver bullet. Nonetheless, attaining the correct mind-set is essential and is the fi rst step in managing IS outsourcing. The lack of such a mind-set is in many cases the cause for the reported high failure rate in IS outsourcing. Knowing yourself and knowing your enemy, as Sun Tsu taught, and knowing the terrain, too—and accordingly adopting a mind-set of identifying and managing risks—are all crucial. This mindset is what makes for successful IS outsourcing.